RELEVANCE OF ABNORMAL UTERINE BLEEDING - Temirova Dilnoza Olimzhonovna; Жумаева Дилноза Рустамовна (TADQIQOTLAR, 2025)
GENERAL INFORMATION Abnormal uterine bleeding (AUB) is bleeding that is excessive in duration (more than 8 days), volume of blood loss (more than 80 ml) and/or frequency (interval less than 24 days). Heavy menstrual bleeding is excessive menstrual blood loss, having a negative impact on the physical, social, emotional and/or material well-being of a woman. The obsolete terms "menorrhagia", "metrorrhagia", "hypermenorrhea", "hypomenorrhea", "menometrorrhagia", "dysfunctional uterine bleeding" are currently replaced by AUB, heavy menstrual bleeding and intermenstrual bleeding. The concept of "AMB" includes the terms: • heavy menstrual bleeding, which means a heavier or longer period of menstruation, • irregular and prolonged menstrual bleeding. However, anemia is not a mandatory criterion for heavy uterine bleeding. It should be noted that AUB includes bleeding from the body and cervix of the uterus, but not from the vagina and vulva. Abnormal uterine bleeding (AUB) not associated with pregnancy has remained one of the leading reasons for visiting a gynecologist for many years; the incidence of AUB is about 30% among patients of reproductive age and can reach 70% in the perimenopausal period. Repeated AUB lead to the development of iron deficiency anemia, significantly reduce the quality of life, and are also associated with additional costs for hygiene products.